Silver particles, method for producing silver particles, paste composition, semiconductor device, and electric and electronic component
By forming silver particles in a silver layer on the surface of the silver powder and used in the paste composition, the problem of insufficient reliability and exothermicity of the bonding material under high temperature conditions is solved, and excellent bonding and heat conduction properties at high temperatures are achieved.
Patent Information
- Application Number
- CN202080059308.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-26
- Filing Date
- 2020-08-07
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2040-08-07
AI Technical Summary
The prior art cannot meet the reliability and exothermic requirements of bonding materials of semiconductor components under high temperature conditions, and the reliability and exothermic properties of solder and silver paste are insufficient.
The silver layer was formed on the surface of the silver powder by liquid phase reduction method, and silver particles having excellent conductivity and sintering properties were prepared, and used in the paste composition as a bonding material for semiconductor devices and electrical and electronic components.
A paste composition with excellent bonding characteristics and thermal conductivity under high temperature conditions is achieved, and the reliability and life of semiconductor devices and electrical and electronic components are improved.
Smart Images

Figure BDA0003514289670000161
Abstract
Description
Technical Field
[0001] The present invention relates to silver particles, a method for producing silver particles, a paste composition, a semiconductor device, and an electric and electronic component. Background Art
[0002] In recent years, the efficiency of semiconductor elements has been continuously improved, and with this, the heat generation of semiconductor elements has increased and the driving temperature has increased. In addition, the bonding material requires reliability and heat dissipation under high temperature conditions. As candidates for bonding materials, solder and silver paste that have been used in the past can be cited, but due to insufficient reliability and heat dissipation, they cannot cope with it, and it is urgently desired to provide a bonding method suitable for high temperature operation. For example, Patent Document 1 proposes a silver sintered (sintered) paste using silver nanoparticles that exhibits excellent conductivity through low temperature sintering.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2013-142173. Summary of the invention
[0006] That is, the present invention relates to the following contents.
[0007] [1] A silver particle comprising: silver powder; and a silver layer composed of primary particles smaller than the silver powder.
[0008] [2] A method for producing silver particles, comprising the step of further forming a silver layer on the surface of (A) silver powder by a liquid phase reduction method.
[0009] [3] A paste composition comprising the silver particles described in [1] or [2] above.
[0010] [4] A semiconductor device formed by bonding using the paste composition described in [3] above.
[0011] [5] An electric or electronic component formed by bonding using the paste composition described in [3] above. DETAILED DESCRIPTION
[0012] Hereinafter, the present invention will be described in detail with reference to one embodiment.
[0013] It should be noted that, in the present invention, "(meth)acrylate" means acrylate and / or methacrylate.
[0014] <Silver particles>
[0015] The silver particles of the present embodiment include: silver powder; and a silver layer composed of primary particles smaller than the silver powder.
[0016] The silver powder constituting the matrix of the silver particles is not particularly limited, and for example, silver powder prepared by a known method such as atomization, electrolysis, chemical reduction, pulverization / crushing, plasma rotating electrode, uniform droplet spray, heat treatment, etc. can be used. From the viewpoint of controlling the particle size and particle shape, the silver powder may be silver powder prepared by atomization, electrolysis or chemical reduction.
[0017] Commercially available products may also be used, and specific examples include Ag-HWQ (manufactured by Fukuda Metal Foil Powder Co., Ltd., D50=1.8 μm, spherical), SL01 (manufactured by Mitsui Mining & Smelting Co., Ltd., D50=1.23 μm, irregular shape), etc. These may be used alone or in combination of two or more.
[0018] The average particle size of the silver powder may be 0.5 μm to 30 μm, greater than 0.5 μm to 20 μm, or 1 μm to 20 μm. In addition, there is no particular limitation on the shape, and examples thereof include spherical, plate-shaped, flake-shaped, scaly, dendritic, rod-shaped, linear, and irregular shapes.
[0019] The average particle size of the silver powder is a particle size (50% particle size D50) at which the cumulative volume is 50% in a particle size distribution measured using a laser diffraction particle size distribution measuring apparatus or the like.
[0020] For example, a silver compound is reduced with a reducing compound, and primary particles of silver released from the silver compound are aggregated to form the silver layer.
[0021] The silver compound may be at least one selected from the group consisting of silver nitrate, silver chloride, silver acetate, silver oxalate, and silver oxide. From the viewpoint of solubility in water, silver nitrate or silver acetate may be used.
[0022] The reducing compound is not particularly limited as long as it has a reducing power to reduce the silver compound and deposit silver.
[0023] As the above-mentioned reducing compound, for example, hydrazine derivatives can be mentioned. As hydrazine derivatives, for example, hydrazine monohydrate, methylhydrazine, ethylhydrazine, n-propylhydrazine, isopropylhydrazine, n-butylhydrazine, isobutylhydrazine, sec-butylhydrazine, tert-butylhydrazine, n-pentylhydrazine, isopentylhydrazine, neopentylhydrazine, tert-pentylhydrazine, n-hexylhydrazine, isohexylhydrazine, n-heptylhydrazine, n-octylhydrazine, n-nonylhydrazine, n-decylhydrazine, n-undecylhydrazine, n-dodecylhydrazine, cyclohexylhydrazine, phenylhydrazine, 4-methylphenylhydrazine, benzylhydrazine, 2-phenylethylhydrazine, 2-hydrazineylethanol, acetylhydrazine, etc. can be mentioned. These can be used alone or in combination of two or more.
[0024] The average particle size of the primary particles may be 10 to 100 nm, 10 to 50 nm, or 20 to 50 nm. When the average particle size of the primary particles is 10 nm or more, the specific surface area will not be too large, and the workability of the paste can be improved. When the average particle size is 100 nm or less, the sintering property is good.
[0025] The average particle size of the primary particles can be obtained by observing the cross-section of spherical silver particles cut by a focused ion beam (FIB) device using a field emission scanning electron microscope (FE-SEM) and averaging the particle sizes of 200 silver particles. Specifically, it can be measured by the method described in the Examples.
[0026] The average particle size of the silver particles may be 0.5 to 5.0 μm, 0.5 to 3.0 μm, or 1.0 to 3.0 μm. When the average particle size of the silver particles is 0.5 μm or more, the storage stability is good, and when the average particle size is 5.0 μm or less, the sintering property is good.
[0027] The average particle size of the silver particles is a particle size at which the cumulative volume accounts for 50% (50% particle size D50) in a particle size distribution measured using a laser diffraction particle size distribution analyzer, and can be specifically measured by the method described in Examples.
[0028] The tap density of the silver particles can be 4.0 to 7.0 g / cm 3 , can be 4.5~7.0g / cm 3 , can also be 4.5~6.5g / cm 3 The tap density of the silver particles is 4.0 g / cm 3 When the above, a large amount of silver particles can be filled in the paste, and the tap density is 7.0g / cm 3 When the content of silver particles in the paste is less than 0.1%, the precipitation of silver particles in the paste can be reduced.
[0029] The tap density of the silver particles can be measured using a tap density measuring device, and specifically, can be measured by the method described in Examples.
[0030] The specific surface area of the silver particles determined by the BET method may be 0.5 to 1.5 m 2 / g, can be 0.5~1.2m 2 / g, and can also be 0.6 to 1.2 m 2 / g. The specific surface area of the silver particles is 0.5m 2 When the surface area of the silver particles is 1.5 m / g or more, the contact between the silver particles can be increased. 2 / g or less, the paste can be made low viscosity.
[0031] The specific surface area of the silver particles can be measured by a BET single-point method based on nitrogen adsorption using a specific surface area measuring device, and specifically, can be measured by the method described in Examples.
[0032] <Method for producing silver particles>
[0033] The method for producing silver particles according to the present embodiment includes a step of further forming a silver layer on the surface of the (A) silver powder by a liquid phase reduction method (hereinafter referred to simply as a silver layer forming step).
[0034] In the silver layer forming step, (A) silver powder, (B) a silver compound, and (C) a reducing compound are mixed in a liquid phase.
[0035] As the (A) silver powder, the (B) silver compound, and the (C) reducing compound, the same as those described in the above section <Silver particles> can be used respectively.
[0036] From the viewpoint of the stability of the complex, the silver compound (B) may be a silver ammonia complex solution.
[0037] The silver-ammine complex solution is not particularly limited and is generally obtained by dissolving a silver compound in aqueous ammonia (see, for example, Japanese Patent Application Laid-Open No. 2014-181399), but may also be prepared by adding an amine compound to a silver compound and then dissolving the compound in alcohol.
[0038] The amount of ammonia added may be 2 to 50 mol, 5 to 50 mol, or 10 to 50 mol per 1 mol of silver in the aqueous solution containing the (B) silver compound. When the amount of ammonia added is within the above range, the average particle size of the primary particles of silver released from the silver compound can be within the above range.
[0039] The silver-ammine complex in the silver-ammine complex solution is reduced by the reducing compound (C) to obtain a slurry containing silver particles.
[0040] The silver ammine complex is reduced by the reducing compound (C) to release silver from the silver ammine complex, and secondary particles formed by aggregation of the primary particles of the silver are formed around the silver powder (A), thereby forming the silver particles of the present embodiment.
[0041] By appropriately adjusting the amount of silver in the silver-ammine complex, the content of the reducing compound (C) and the average particle size of the added silver powder (A), the aggregation of the primary particles can be controlled and the average particle size of the obtained secondary particles (silver particles) can be set within the above range.
[0042] The content of the reducing compound (C) may be 0.25 to 20 mol, 0.25 to 10 mol, or 1.0 to 5.0 mol per 1 mol of silver in the silver-ammine complex.
[0043] Furthermore, the temperature of the silver ammonia complex solution during the reduction of the silver ammonia complex may be less than 30° C. or may be 0 to 20° C. When the temperature of the silver ammonia complex solution is within this range, the aggregation of the primary particles can be controlled, and the average particle size of the obtained secondary particles can be within the above range.
[0044] By further adding (D) an organic protective compound to the silver particle-containing slurry obtained as described above, a protective group can be introduced into the silver particles in the silver particle-containing slurry.
[0045] Examples of the (D) organic protective compound include carboxylic acid, alkylamine, carboxylic acid amine salt, amide, etc. From the viewpoint of particle stability, the (D) organic protective compound may be at least one selected from carboxylic acid, alkylamine, and carboxylic acid amine salt, and may be a carboxylic acid from the viewpoint of improving dispersibility.
[0046] Examples of carboxylic acids include monocarboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, caprylic acid, nonanoic acid, capric acid, oleic acid, stearic acid, and isostearic acid; dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and diglycolic acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, salicylic acid, and gallic acid; hydroxy acids such as glycolic acid, lactic acid, tartronic acid, malic acid, glyceric acid, hydroxybutyric acid, tartaric acid, citric acid, and isocitric acid, etc. These may be used alone or in combination of two or more.
[0047] The amount of the organic protective compound (D) may be 1 to 20 mmol, 1 to 10 mmol, or 1 to 5 mmol relative to 1 mol of the silver particles. When the amount of the organic protective compound is 1 mmol or more, the silver particles can be dispersed in the resin, and when the amount of the organic protective compound is 20 mmol or less, the silver particles can be dispersed in the resin without impairing the sinterability.
[0048] (Mixture Formation)
[0049] (A) Silver powder, (B) Silver compound and (C) Reducing compound are mixed in a reaction container, and (D) Organic protective compound is further mixed as required. The order of mixing these compounds is not particularly limited, and the above compounds can be mixed in any order.
[0050] The silver particles obtained by the method for manufacturing silver particles of this embodiment are secondary particles formed by agglomeration of nano-sized silver primary particles on the surface of silver powder, thereby maintaining the high activity of the surface of the above-mentioned silver primary particles and having sintering properties (self-sintering properties) between the secondary particles under low temperature conditions. In addition, the sintering between the silver particles and the sintering of the silver particles and the bonding parts are carried out simultaneously. Therefore, by using the above-mentioned silver particles, a paste composition with excellent thermal conductivity and adhesive properties can be obtained.
[0051] <Ointment Composition>
[0052] The paste composition of this embodiment contains the above-mentioned silver particles. Therefore, the paste composition of this embodiment has low viscosity and good dispersibility, and can obtain a cured product with excellent bonding properties and thermal conductivity, small volume shrinkage and excellent low stress properties. The paste composition of this embodiment can be used as a die bonding material for element bonding, a heat dissipation component bonding material, etc.
[0053] The paste composition of the present embodiment can form an adhesive material (paste) having an appropriate viscosity by containing a thermosetting resin.
[0054] As long as the thermosetting resin is a thermosetting resin commonly used as an adhesive, it can be used without particular limitation. The above-mentioned thermosetting resin can be a liquid resin, or a resin that is liquid at room temperature (25° C.). As the above-mentioned thermosetting resin, it can be at least one selected from cyanate resin, epoxy resin, acrylic resin and maleimide resin. These can be used alone or in combination of two or more.
[0055] Cyanate resin is a compound having -NCO groups in the molecule, and is a resin that forms a three-dimensional network structure and cures by reacting the -NCO groups by heating. Specific examples of cyanate resin include 1,3-dicyanatobenzene, 1,4-dicyanatobenzene, 1,3,5-tricyanobenzene, 1,3-dicyanatonaphthalene, 1,4-dicyanatonaphthalene, 1,6-dicyanatonaphthalene, 1,8-dicyanatonaphthalene, 2,6-dicyanatonaphthalene, 2,7-dicyanatonaphthalene, 1,3,6-tricyanonaphthalene, 4,4'-dicyanatobiphenyl, bis(4-cyanatophenyl)methane, bis(3,5 2,2-bis(4-cyanatophenyl)propane, 2,2-bis(3,5-dibromo-4-cyanatophenyl)propane, bis(4-cyanatophenyl)ether, bis(4-cyanatophenyl)sulfide, bis(4-cyanatophenyl)sulfone, tris(4-cyanatophenyl)phosphite, tris(4-cyanatophenyl)phosphate, and cyanate esters obtained by the reaction of novolac resin with cyanogen halide, etc. In addition, a prepolymer having a triazine ring formed by trimerizing the cyanate group of these multifunctional cyanate resins can also be used. The prepolymer is obtained by, for example, polymerizing the above-mentioned multifunctional cyanate resin monomers using an acid such as an inorganic acid or Lewis acid, a base such as sodium alcoholate or a tertiary amine, or a salt such as sodium carbonate as a catalyst.
[0056] As a curing accelerator for cyanate resin, generally known substances can be used. For example, organic metal complexes such as zinc octylate, tin octylate, cobalt naphthenate, zinc naphthenate, and ferric acetylacetonate; metal salts such as aluminum chloride, tin chloride, and zinc chloride; and amines such as triethylamine and dimethylbenzylamine can be mentioned, but are not limited to these. These curing accelerators can be used alone or in combination of two or more.
[0057] Epoxy resin is a compound having one or more glycidyl groups in the molecule, and is a resin that forms a three-dimensional network structure and solidifies by heating the glycidyl groups to react. The above-mentioned epoxy resin can also be a compound containing two or more glycidyl groups in one molecule. This is because a compound having only one glycidyl group cannot exhibit sufficient cured product properties even if reacted. A compound containing two or more glycidyl groups in one molecule can be obtained by epoxidizing a compound having two or more hydroxyl groups. Examples of such compounds include bisphenol compounds such as bisphenol A, bisphenol F, and biphenol, or their derivatives; diols having an alicyclic structure such as hydrogenated bisphenol A, hydrogenated bisphenol F, hydrogenated biphenol, cyclohexanediol, cyclohexanedimethanol, and cyclohexanediethanol, or their derivatives; difunctional compounds formed by epoxidation of aliphatic diols such as butanediol, hexanediol, octanediol, nonanediol, and decanediol, or their derivatives; trifunctional compounds formed by epoxidation of compounds having a trihydroxyphenylmethane skeleton or an aminophenol skeleton; polyfunctional compounds formed by epoxidation of phenol novolac resins, o-cresol novolac resins, phenol aralkyl resins, biphenyl aralkyl resins, and naphthol aralkyl resins, etc., but are not limited to these.
[0058] In addition, in order to make the paste composition in a paste state at room temperature (25°C), the epoxy resin may be a compound that is liquid at room temperature (25°C) alone or in a mixture. A reactive diluent may also be used as is usually done. Examples of the reactive diluent include monofunctional aromatic glycidyl ethers such as phenyl glycidyl ether and cresyl glycidyl ether, and aliphatic glycidyl ethers.
[0059] As the curing agent of epoxy resin, for example, aliphatic amine, aromatic amine, dicyandiamide, dihydrazide compound, acid anhydride, phenolic resin, etc. can be mentioned. As dihydrazide compound, carboxylic acid dihydrazide such as adipic acid dihydrazide, dodecanoic acid dihydrazide, isophthalic acid dihydrazide, p-oxybenzoic acid dihydrazide, etc. can be mentioned. As acid anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, cross-methylenetetrahydrophthalic anhydride, dodecenyl succinic anhydride, the reaction product of maleic anhydride and polybutadiene, copolymer of maleic anhydride and styrene, etc. can be mentioned.
[0060] Furthermore, in order to promote curing, a curing accelerator can be added. As the curing accelerator of the epoxy resin, there can be mentioned imidazoles, triphenylphosphine or tetraphenylphosphine and their salts, amine compounds such as diazabicycloundecene and their salts, etc. The above-mentioned curing accelerator can be, for example, 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-C 11 H 23The imidazole compound such as imidazole or an adduct of 2-methylimidazole and 2,4-diamino-6-vinyltriazine may have a melting point of 180° C. or higher.
[0061] Examples of the acrylic resin include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 1,2-cyclohexanediol mono(meth)acrylate, 1,3-cyclohexanediol mono(meth)acrylate, 1,4-cyclohexanediol mono(meth)acrylate, 1,2-cyclohexanedimethanol mono(meth)acrylate, 1,3-cyclohexanedimethanol mono(meth)acrylate, 1,4-cyclohexanedimethanol mono(meth)acrylate, 1,2-cyclohexanedimethanol mono(meth)acrylate, (Meth)acrylates having a hydroxyl group such as mono(meth)acrylate, 1,3-cyclohexanediethanol mono(meth)acrylate, 1,4-cyclohexanediethanol mono(meth)acrylate, glycerol mono(meth)acrylate, glycerol di(meth)acrylate, trimethylolpropane mono(meth)acrylate, trimethylolpropane di(meth)acrylate, pentaerythritol mono(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, neopentyl glycol mono(meth)acrylate, and (meth)acrylates having a carboxyl group obtained by reacting these (meth)acrylates having a hydroxyl group with a dicarboxylic acid or a derivative thereof. Examples of the dicarboxylic acid that can be used herein include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, maleic acid, fumaric acid, phthalic acid, tetrahydrophthalic acid, hexahydrophthalic acid, and derivatives thereof.
[0062] Examples of acrylic resins include compounds having a (meth)acryloyl group such as polyether, polyester, polycarbonate, poly(meth)acrylate, etc. having a molecular weight of 100 to 10,000; (meth)acrylate having a hydroxyl group; and (meth)acrylamide having a hydroxyl group.
[0063] Maleimide resin is a compound containing more than one maleimide group in one molecule, and is a resin that forms a three-dimensional network structure and solidifies by reacting the maleimide group by heating. As maleimide resin, for example, bismaleimide resins such as N, N'-(4,4'-diphenylmethane) bismaleimide, bis(3-ethyl-5-methyl-4-maleimidephenyl) methane, and 2,2-bis[4-(4-maleimidephenoxy)phenyl]propane can be cited. Maleimide resin can be a compound obtained by the reaction of dimer acid diamine with maleic anhydride; a compound obtained by the reaction of maleimidoacetic acid, maleimidocaproic acid and polyol. The above-mentioned maleimidoamino acid is obtained by reacting maleic anhydride with aminoacetic acid or aminocaproic acid. The polyol may be a polyether polyol, a polyester polyol, a polycarbonate polyol, or a poly(meth)acrylate polyol, and may be a polyol not containing an aromatic ring.
[0064] The content of the thermosetting resin can be 1 to 20 parts by mass, or 5 to 18 parts by mass, relative to 100 parts by mass of silver particles. When the thermosetting resin is 1 part by mass or more, the adhesiveness brought by the thermosetting resin can be fully obtained. When the thermosetting resin is 20 parts by mass or less, the proportion of the silver component can be controlled to be reduced, high thermal conductivity can be fully ensured, and heat release can be improved. In addition, the organic component will not be excessive, and the degradation caused by light and heat can be suppressed. As a result, the life of the light-emitting device can be improved.
[0065] From the viewpoint of workability, the paste composition of the present embodiment may also contain a diluent. As a diluent, for example, butyl carbitol, cellosolve acetate, ethyl cellosolve, butyl cellosolve, butyl cellosolve acetate, butyl carbitol acetate, diethylene glycol dimethyl ether, diacetone alcohol, N-methyl-2-pyrrolidone (NMP), dimethylformamide, N, N-dimethylacetamide (DMAc), γ-butyrolactone, 1,3-dimethyl-2-imidazolidinone, 3,5-dimethyl-1-adamantanamine (DMA), etc. can be cited. These can be used alone or in combination of two or more.
[0066] When the paste composition of the present embodiment contains a diluent, the content of the diluent may be 3 to 20 parts by mass, 4 to 15 parts by mass, or 4 to 10 parts by mass relative to 100 parts by mass of the silver particles. When the content of the diluent is 3 parts by mass or more, the viscosity can be reduced by dilution, and when the content of the diluent is 20 parts by mass or less, the generation of voids during the curing of the paste composition of the present embodiment can be controlled.
[0067] In addition to the above components, the paste composition of this embodiment may also contain, as required, a curing accelerator that is usually formulated in such a composition; a stress reducing agent such as rubber or silicone; a coupling agent; a defoaming agent; a surfactant; a coloring agent such as a pigment or dye; a polymerization initiator; various polymerization inhibitors; an antioxidant; a solvent; and various other additives. Each of these additives may be used alone or in combination of two or more.
[0068] The paste composition of the present embodiment can be prepared by fully mixing the above-mentioned silver particles, the thermosetting resin, the diluent and various additives as required, further kneading the mixture with a disperser, a kneader, a three-roll mill or the like, and then degassing the mixture.
[0069] The thermal conductivity of the cured product of the paste composition of the present embodiment may be 35 W / m·K or more, or 40 W / m·K or more.
[0070] The above-mentioned thermal conductivity can be measured by the method described in Examples.
[0071] The viscosity of the paste composition of the present embodiment may be 70 to 200 Pa·s, or 100 to 200 Pa·s.
[0072] The above viscosity is a value measured using an E-type viscometer (3° cone angle) at 25° C. Specifically, it can be measured by the method described in Examples.
[0073] <Semiconductor devices and electrical and electronic components>
[0074] The semiconductor device and the electric and electronic component of the present embodiment are bonded using the paste composition and therefore have excellent reliability.
[0075] The semiconductor device of this embodiment is formed by bonding a semiconductor element to a substrate as an element supporting member using the above-mentioned paste composition. That is, here, the paste composition is used as a die bonding material, and the semiconductor element and the substrate are bonded and fixed by the die bonding material.
[0076] Here, the semiconductor element may be a known semiconductor element, for example, a transistor, a diode, etc. Further, as the semiconductor element, a light-emitting element such as an LED may be mentioned. In addition, there is no particular limitation on the type of the light-emitting element, for example, an element formed by forming a nitride semiconductor such as InN, AlN, GaN, InGaN, AlGaN, InGaAlN, etc. as a light-emitting layer on a substrate by a MOBVC method or the like may be mentioned.
[0077] In addition, examples of the element supporting member include supporting members formed of materials such as copper, copper-plated copper, PPF (pre-plated lead frame), glass epoxy resin, and ceramics.
[0078] By using the above-mentioned die bonding material, the semiconductor element can also be bonded to a substrate that has not been subjected to metal plating. Compared with the past, the connection reliability of the semiconductor device obtained in this way to temperature cycling after mounting is significantly improved. In addition, since the resistance value is sufficiently small and the change over time is small, it has the advantages of less reduction in output over time even if driven for a long time and a long life.
[0079] In addition, the electric and electronic component of the present embodiment is formed by bonding a heat dissipating component to a heat generating component using the paste composition. That is, the paste composition is used as a heat dissipating component bonding material, and the heat dissipating component and the heat generating component are bonded and fixed by the paste composition.
[0080] The heat generating component may be the semiconductor element or a component having the semiconductor element, or may be a heat generating component other than the semiconductor element. As heat generating components other than the semiconductor element, optical pickups, power transistors, etc. may be cited. In addition, as heat releasing components, heat sinks, heat spreaders, etc. may be cited.
[0081] As described above, by using the heat dissipating component bonding material to bond the heat dissipating component to the heat generating component, the heat generated by the heat generating component can be efficiently released to the outside through the heat dissipating component, and the temperature rise of the heat generating component can be suppressed. In addition, the heat generating component and the heat dissipating component can be directly bonded by the heat dissipating component bonding material, or can be indirectly bonded by sandwiching other components with high thermal conductivity.
[0082] Example
[0083] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples.
[0084] (Manufacturing of Silver Particles)
[0085] [Synthesis example 1]
[0086] 40 g of silver nitrate (manufactured by Toyo Chemical Industry Co., Ltd.) was dissolved in 10 L of ion exchange water to prepare a silver nitrate aqueous solution, to which 203 mL of ammonia water with a concentration of 26% by mass was added and stirred to obtain a silver ammonia complex aqueous solution. 50 g of silver powder (product name: Ag-HWQ 1.5 μm; manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.; average particle size: 1.8 μm) was added to the aqueous solution to prepare a silver ammonia complex aqueous solution in which silver powder was dispersed. The liquid temperature was set to 10°C, and 28 mL of a 20% by mass hydrazine monohydrate aqueous solution (manufactured by Hayashi Junyaku Industries Co., Ltd.) was added dropwise for 60 seconds while stirring to precipitate silver on the surface of the silver powder to obtain a slurry containing silver particles. Oleic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) was added at 1% by mass relative to the amount of silver to the slurry, and stirred for 10 minutes. The slurry was filtered, and the filter residue was washed with water and methanol, and dried at 60° C. for 24 hours in a vacuum environment to obtain silver particles 1 .
[0087] In addition, the cross section of the obtained silver particle 1 was observed using a field emission scanning electron microscope (FE-SEM) (JSM-6700F manufactured by JEOL Ltd. (JEOL)), and it was confirmed that the silver particle 1 was agglomerated around the silver powder and a silver layer was formed on the surface of the silver powder. In addition, the average particle size of the primary particles of silver forming the silver layer was 20 nm, and the average particle size of the secondary particles formed by the aggregation of the primary particles was 1.9 μm. The tap density of the obtained silver particle 1 was 5.7 g / cm 3 , with a specific surface area of 1.0m 2 / g.
[0088] [Synthesis example 2]
[0089] 40 g of silver nitrate (manufactured by Toyo Chemical Industry Co., Ltd.) was dissolved in 10 L of ion exchange water to prepare a silver nitrate aqueous solution, to which 203 mL of ammonia water with a concentration of 26% by mass was added and stirred to obtain a silver ammonia complex aqueous solution. 50 g of silver powder (product name: AgS1.0; manufactured by Tokuri Honten Co., Ltd.; average particle size: 1.59 μm) was added to the aqueous solution to prepare a silver ammonia complex aqueous solution in which silver powder was dispersed. The liquid temperature was set to 10°C, and 28 mL of a 20% by mass hydrazine monohydrate aqueous solution (manufactured by Hayashi Jun Chemical Industry Co., Ltd.) was added dropwise for 60 seconds while stirring to precipitate silver on the surface of the silver powder to obtain a slurry containing silver particles. Oleic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) was added in an amount of 1% by mass relative to the amount of silver to the slurry, and stirred for 10 minutes. The slurry was filtered, and the filter residue was washed with water and methanol, and dried at 60°C for 24 hours in a vacuum environment to obtain silver particles 2.
[0090] [Synthesis example 3]
[0091] 40 g of silver nitrate (manufactured by Toyo Chemical Industry Co., Ltd.) was dissolved in 10 L of ion exchange water to prepare a silver nitrate aqueous solution, to which 203 mL of ammonia water with a concentration of 26% by mass was added and stirred to obtain a silver ammonia complex aqueous solution. 50 g of silver powder (product name: AgS2.0; manufactured by Tokuri Honten Co., Ltd.; average particle size: 2.45 μm) was added to the aqueous solution to prepare a silver ammonia complex aqueous solution in which silver powder was dispersed. The liquid temperature was set to 10° C., and 28 mL of a 20% by mass hydrazine monohydrate aqueous solution (manufactured by Hayashi Jun Chemical Industry Co., Ltd.) was added dropwise for 60 seconds while stirring to precipitate silver on the surface of the silver powder to obtain a slurry containing silver particles. Oleic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) was added in an amount of 1% by mass relative to the amount of silver to the slurry, and stirred for 10 minutes. The slurry was filtered, and the filter residue was washed with water and methanol, and dried at 60° C. for 24 hours in a vacuum environment to obtain silver particles 3.
[0092] [Synthesis Example 4]
[0093] 40 g of silver nitrate (manufactured by Toyo Chemical Industry Co., Ltd.) was dissolved in 10 L of ion exchange water to prepare a silver nitrate aqueous solution, to which 203 mL of ammonia water with a concentration of 26% by mass was added and stirred to obtain a silver ammonia complex aqueous solution. 50 g of silver powder (product name: AgS1.0; manufactured by Tokuri Honten Co., Ltd.; average particle size: 1.59 μm) was added to the aqueous solution to prepare a silver ammonia complex aqueous solution in which silver powder was dispersed. The liquid temperature was set to 10°C, and 20 mL of a 20% by mass hydrazine monohydrate aqueous solution (manufactured by Hayashi Jun Chemical Industry Co., Ltd.) was added dropwise for 60 seconds while stirring to precipitate silver on the surface of the silver powder to obtain a slurry containing silver particles. Oleic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) was added in an amount of 1% by mass relative to the amount of silver to the slurry, and stirred for 10 minutes. The slurry was filtered, and the filter residue was washed with water and methanol, and dried at 60°C for 24 hours in a vacuum environment to obtain silver particles 4.
[0094] Silver Particles 1 to 4 obtained in Synthesis Examples 1 to 4 were evaluated by the following method.
[0095] [Average particle size of primary particles]
[0096] To 1020 mL of the silver ammine complex aqueous solution obtained in each of the above synthesis examples, 2.8 mL of a 20% by mass hydrazine monohydrate aqueous solution was added dropwise over 60 seconds to perform solid-liquid separation. The obtained solid was washed with pure water and dried at 60° C. for 24 hours under a vacuum environment to obtain silver particles, which were used to measure the average particle size of the primary particles.
[0097] The average particle size of the primary particles was determined by observing the cross-section of spherical silver particles cut by a focused ion beam (FIB) device (JEM-9310FIB manufactured by JEOL Ltd. (JEOL)) using a field emission scanning electron microscope (FE-SEM) (JSM-6700F manufactured by JEOL Ltd. (JEOL)) and averaging the particle sizes of 200 silver particles.
[0098] [Average particle size of secondary particles]
[0099] The average particle size of the secondary particles was determined from the particle size at which the cumulative volume was 50% (50% particle size D50) in the particle size distribution measured using a laser diffraction particle size distribution analyzer (manufactured by Shimadzu Corporation, trade name: SALAD-7500nano).
[0100] [Tap density]
[0101] The mass per unit volume of the silver particles in the vibrating container (unit: g / cm) was measured using a tap density meter (Tap-Pak Volumeter, manufactured by Thermo Fisher Scientific, USA). 3 ) was used to determine the tap density (TD).
[0102] [Specific surface area]
[0103] After degassing at 60° C. for 10 minutes, the specific surface area was measured by the BET single-point method based on nitrogen adsorption using a specific surface area measuring device (Monosorb, manufactured by Quanatachrome Corporation, USA).
[0104] Table 1
[0105] Synthesis example 1 Synthesis example 2 Synthesis example 3 Synthesis example 4 Silver particles 1 Silver particles 2 Silver particles 3 Silver particles 4 Average particle size of primary particles [nm] 20 20 20 30 Average particle size of secondary particles [μm] 1.9 2.2 2.7 2.0 <![CDATA[Tap density [g / cm 3 > 5.7 5.0 5.51 5.25 <![CDATA[Specific surface area [m 2 / g]]]> 1.0 1.2 0.8 0.9
[0106] [Examples 1 to 9, Comparative Examples 1 to 4]
[0107] The ingredients were mixed according to the ratio in Table 2 and kneaded using a three-roll mill to obtain a paste composition. The obtained paste composition was evaluated by the method described below. The results are shown in Table 2. It should be noted that in Table 2, blank columns indicate that no compounding was performed.
[0108] The materials described in Table 2 used in Examples and Comparative Examples are as follows.
[0109] [Silver Particles X]
[0110] (Silver particles 1): Silver particles obtained in Synthesis Example 1 (average particle size of primary particles: 20 nm; average particle size of secondary particles: 1.9 μm)
[0111] (Silver particles 2): Silver particles obtained in Synthesis Example 2 (average particle size of primary particles: 20 nm; average particle size of secondary particles: 2.2 μm)
[0112] (Silver particles 3): Silver particles obtained in Synthesis Example 3 (average particle size of primary particles: 20 nm; average particle size of secondary particles: 2.7 μm)
[0113] (Silver particles 4): Silver particles obtained in Synthesis Example 4 (average particle size of primary particles: 30 nm; average particle size of secondary particles: 2.0 μm)
[0114] [Silver Particles Obtained by a Production Method Other Than the Production Method of Silver Particles of the Present Embodiment (Silver Particles Y)]
[0115] ·TC-505C (manufactured by Deli Honten Co., Ltd.; trade name; average particle size: 1.93μm; tap density: 6.25g / cm 3 ; Specific surface area: 0.65m 2 / g)
[0116] Ag-HWQ 1.5μm (manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.; trade name; average particle size: 1.8μm; tap density: 3.23g / cm 3 ; Specific surface area: 0.5m 2 / g)
[0117] AgC-221PA (manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.; trade name; average particle size: 7.5 μm; tap density: 5.7 g / cm 3 ; Specific surface area: 0.3m 2 / g)
[0118] DOWA Ag nano powder-1 (manufactured by DOWA Electronics Co., Ltd.; trade name; average particle size: 20 nm)
[0119] DOWA Ag nano powder-2 (manufactured by DOWA Electronics Co., Ltd.; trade name; average particle size: 60 nm)
[0120] [Thermosetting resin]
[0121] Epoxy resin: (Mitsubishi Chemical Corporation; trade name: YL983U)
[0122] Acrylic resin (manufactured by KJ Chemicals Corporation; trade name: HEAA (registered trademark))
[0123] ·Bisphenol F (manufactured by Honshu Chemical Industry Co., Ltd.; trade name: Bisphenol F)
[0124] [Thinner]
[0125] ·Butyl carbitol (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0126] [Other ingredients]
[0127] Imidazole (manufactured by Shikoku Chemical Industry Co., Ltd.; trade name: Curezol 2P4MHZ-PW)
[0128] Dicumyl peroxide (manufactured by NOF Corporation; trade name: Percumyl (registered trademark) D)
[0129] <Evaluation Method>
[0130] [Thermal conductivity]
[0131] Measuring instrument: LFA-502 (manufactured by Kyoto Electronics Co., Ltd.)
[0132] Measurement method: Laser flash method
[0133] The thermal conductivity of the cured product of the paste composition was measured by a laser flash method using the above-mentioned measuring instrument in accordance with JIS R 1611-1997.
[0134] [Volume resistivity]
[0135] The paste composition was applied to a glass substrate (thickness 1 mm) by screen printing to a thickness of 30 μm and cured at 190° C. for 60 minutes. The volume resistivity of the obtained wiring was measured by a four-probe method using a product name “MCP-T600” (manufactured by Mitsubishi Chemical Corporation).
[0136] [Viscosity]
[0137] The value under the conditions of a temperature of 25° C. and a rotation speed of 0.5 rpm was measured using an E-type viscometer (manufactured by Toki Kogyo Co., Ltd.; product name: VISCOMETER-TV22; applied cone-plate rotor: 3°×R17.65).
[0138] [Applicable period]
[0139] The number of days until the viscosity of the paste composition when left in a thermostatic chamber at 25° C. thickened to 1.5 times or more of the initial viscosity was measured.
[0140] [Warp]
[0141] The package warpage of a semiconductor package was measured at room temperature (25°C). The semiconductor package was made by mounting a 8mm×8mm silicon chip with a gold-plated back surface and a gold-deposited layer on a copper substrate plated with Ag on the surface using a paste composition, and curing at 190°C for 60 minutes. The measurement device used a projection corrugation measurement device (ThermoireAXP: manufactured by Akrometrix, USA), and the measurement was performed in accordance with JEITA ED-7306 of the Electronics and Information Technology Industry Association standard. Specifically, a virtual plane calculated by the least squares method for all data on the substrate surface of the measurement area was used as a reference plane, and the value of |A|+|B| (coplanarity) when the maximum value in the vertical direction from the reference plane was set to A and the minimum value was set to B was used as the package warpage value.
[0142] [Hot and cold cycle test]
[0143] Using the paste composition, a 8mm×8mm silicon chip with a gold-plated back surface and a gold-deposited layer on the bonding surface was mounted on a copper frame plated with Ag on the surface, and heated and cured at 190°C for 60 minutes to prepare a semiconductor package. The semiconductor package was subjected to a hot and cold cycle treatment (the operation of heating from -55°C to 150°C and then cooling to -55°C was set as 1 cycle, and it was cycled 2000 times), and the chip after treatment was observed by an ultrasonic microscope (FineSAT II, manufactured by Hitachi Power Solutions Co., Ltd.) to see if it was peeled off, and the evaluation was performed according to the following criteria.
[0144] (Judgment Criteria)
[0145] A: No peeling
[0146] C: With peeling
[0147] Table 2
[0148]
[0149] Examples 1 to 9 using the paste composition containing the silver particles of the present invention all have low viscosity and excellent dispersibility. It can be seen that the cured product of the paste composition has high thermal conductivity and less warping. In addition, it can be seen that the semiconductor packages obtained using the above paste composition have excellent adhesion without chip peeling after the hot and cold cycle test.
Claims
1. A silver particle, wherein: It comprises: silver powder; and a silver layer formed by agglomeration of primary particles having an average particle size of 20 to 50 nm smaller than the silver powder, The average particle size of the silver powder is greater than or equal to 1 μm and less than or equal to 2.45 μm. The specific surface area of the silver particles determined by the BET method is 0.5 to 1.5 m 2 / g, The silver particles have a protecting group of at least one (D) organic protecting compound selected from the group consisting of carboxylic acid, alkylamine and carboxylic acid amine salt.
2. The silver particles according to claim 1, wherein Tap density is 4.0~7.0g / cm 3 .
3. A method for producing silver particles, wherein: The method comprises the step of forming a silver layer composed of aggregated primary particles having an average particle size of 20 to 50 nm on the surface of the silver powder (A) having an average particle size of 1 μm or more and 2.45 μm or less by a liquid phase reduction method, In the above step, (A) silver powder, (B) a silver compound, and (C) a reducing compound are mixed in a liquid phase. In the above step, at least one (D) organic protective compound selected from carboxylic acid, alkylamine and carboxylic acid amine salt is further added. The specific surface area of the silver particles determined by the BET method is 0.5 to 1.5 m 2 / g.
4. The method for producing silver particles according to claim 3, wherein: The (A) silver powder is prepared by an atomization method, an electrolysis method or a chemical reduction method.
5. The method for producing silver particles according to claim 3 or 4, wherein: The (B) silver compound is at least one selected from the group consisting of silver nitrate, silver chloride, silver acetate, silver oxalate, and silver oxide.
6. A paste composition, wherein: It contains the silver particles according to claim 1 or 2.
7. A semiconductor device, wherein: The bonding is performed using the paste composition according to claim 6.
8. An electrical or electronic component, wherein: The bonding is performed using the paste composition according to claim 6.
Citation Information
Patent Citations
Method for producing silver nanoparticle, silver nanoparticle, and silver coating composition
JP2013142173A
Method for manufacturing silver particles
JP2014181399A
Superfine silver particulate-stuck silver powder, and method for producing the superfine silver particulate-stuck silver powder
JP2005146408A